Perancangan Website Dinas Pendidikan Pemuda Dan Olah Raga (Studi Kasus Dinas Pendidikan Pemuda Dan Olah Raga Kabupaten Kebumen) - Waluyo, Ari; Fatich, El Vionna Laellyn Nurul (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The research have goal to design the Dinas Pendidikan, Pemuda dan Olah Raga website using PHP programming language and MySQL database at Dinas Pendidikan, Pemuda dan Olah Raga in Kebumen. Reseach method have used in this research is qualitative with descriptive method. Data collection technique is observation, interview, and literature review which have connection with main problem. The system development method which used is SDLC (System Development Life Circle). From the result of research have problems such as the menu provided too much and the information presented is not grouped properly. It made the user still feel difficulty in finding the needed information. There are recommendations which give to solving the problem are: 1) grouping the menus to easier finding informations, 2) re-design website that can show the information with categories, and 3) make the user-friendly website design.